A method for surface modification of polyetheretherketone material and polyetheretherketone surface composition obtained therefrom

Plasma immersion ion implantation with argon and copper ions on PEEK surfaces forms a nanostructured surface that enhances biocompatibility and antibacterial properties, improving bone integration and cell adhesion, addressing the limitations of current PEEK materials.

CN115704089BActive Publication Date: 2024-12-27SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110925785.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-12
Publication Date
2024-12-27
Estimated Expiration
2041-08-12

AI Technical Summary

Technical Problem

Existing polyetheretherketone (PEEK) materials face challenges in achieving both bone integration and antibacterial properties due to poor biocompatibility and susceptibility to bacterial growth, with current surface modification methods being inefficient and unsuitable for large-scale production.

Method used

A method involving plasma immersion ion implantation is used to etch the PEEK surface with argon ions to form a nanostructure, followed by copper ion implantation to introduce biological activity and antibacterial properties, utilizing argon and copper ions to create a unique nanoparticle structure that enhances surface area and contact with cells and bacteria.

Benefits of technology

The modified PEEK surface exhibits improved biocompatibility, bone integration, and antibacterial properties, supporting cell adhesion and proliferation, while effectively inhibiting bacterial growth, thus addressing the limitations of existing surface modification techniques.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115704089B_ABST
    Figure CN115704089B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for surface modification of polyetheretherketone material and a polyetheretherketone surface composition obtained therefrom. The method comprises: a first step of injecting argon ions into the surface of the polyetheretherketone material by plasma immersion injection; a second step of placing the polyetheretherketone material with the argon ions injected on the surface for a period of time; and a third step of plasma immersion injecting copper ions into the surface of the polyetheretherketone material after placement. The method improves the biocompatibility and antibacterial properties of the polyetheretherketone material by plasma immersion ion injection technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for surface modification of a polyetheretherketone material and a polyetheretherketone surface composition obtained therefrom. Background Art

[0002] In recent years, with the continuous improvement of biomaterial preparation technology, application fields and theoretical development, the application prospects of polymer implant materials are broader. The elastic modulus of medical polyetheretherketone (PEEK) material is most compatible with human bone tissue, which can effectively reduce bone absorption and bone atrophy caused by stress shielding effect. At the same time, polyetheretherketone material has outstanding fatigue resistance and is suitable for medical implant devices. However, PEEK has poor biological activity and is not easy to bond with human bone tissue after implantation in the human body. PEEK is prone to bacterial growth after implantation, which limits its application as a long-term implant material. At present, the main method for surface modification of polyetheretherketone material is chemical grafting. This method has a shallow modification depth, poor effect, long reaction time, low efficiency, and is not conducive to large-scale production.

[0003] How to modify the surface of polyetheretherketone materials in a simple and easy way to improve the biocompatibility and antibacterial properties of polyetheretherketone materials has become one of the current research hotspots. Surface structure is an important factor that determines the biological properties of the material surface. Bones, teeth, DNA and proteins in the human body all have micro / nano structures with specific functions. Studies have shown that nanoscale materials play an important role in evoking appropriate cell responses, regulating cell adhesion and differentiation on the surface of materials, promoting bone regeneration, and improving and prolonging the use effect and life of implants. In addition, nanostructures can stimulate (promote) osteoblast-related cell adhesion, proliferation and osteogenic differentiation, which has been widely reported in the field of hard tissue implant materials. In addition, nanostructures of special sizes also have an inhibitory effect on bacterial migration, proliferation and bacterial biofilm formation. Therefore, constructing micro / nano structures is an important choice for surface functionalization of polyetheretherketone materials based on their practical applications.

[0004] However, it is difficult to achieve both bone integration and antibacterial properties by relying solely on micro / nanostructures. Copper is an important trace element required for osteogenesis and angiogenesis. An appropriate amount of copper supplementation has a very positive effect on the regulation of bone homeostasis. It can not only accelerate the maturation and differentiation of osteoblasts and promote the formation and reconstruction of new bones, but also inhibit the formation of osteoclast pits and reduce the bone resorption activity of osteoclasts. Copper also has a broad-spectrum antibacterial property and is not easy to develop drug resistance. An appropriate amount of copper plays an important role in maintaining the normal immune function of the human body, helps to reduce inflammatory responses, and promote wound healing. How to construct a nanostructure on the surface of polyetheretherketone material and introduce copper at the same time to achieve both bone integration and antibacterial properties is a technical problem to be solved in the present invention. Summary of the invention

[0005] In view of the above problems, the present invention provides a method for surface modification of polyetheretherketone material and a polyetheretherketone surface composition obtained therefrom. The method improves the biocompatibility and antibacterial property of polyetheretherketone material through plasma immersion ion implantation technology.

[0006] In a first aspect, the present invention provides a method for surface modification of a polyetheretherketone material, comprising: a first step of implanting argon ions on the surface of the polyetheretherketone material by plasma immersion implantation;

[0007] The second step is to place the polyetheretherketone material with argon ions implanted on the surface for a period of time;

[0008] The third step is to implant copper ions on the surface of the polyetheretherketone material by plasma immersion.

[0009] The modification method of the present invention uses argon ion implantation to etch the surface of polyetheretherketone to form a unique nanostructure (e.g., peanut-like nanoparticles), which is conducive to increasing the surface area (contact area) of the polyetheretherketone material. Then, copper ion implantation is used to introduce copper elements that impart biological activity and antibacterial properties to the etched surface of the polyetheretherketone. The surface biocompatibility, bone integration and antibacterial properties of the polyetheretherketone material modified by this method are significantly improved, and it has potential prospects for loading bone-inducing growth factors and antibacterial drugs.

[0010] Preferably, the argon ion injection time of the first process is 10 to 20 minutes. The role of the argon ion injection in the first process is to clean and activate the surface of the polyetheretherketone sample and break at least part of the molecular chain. The amorphous area with more molecular chain breaks has a lower density and sparse atomic nuclei. It is compacted by collision under the subsequent copper ion injection, and the copper ions are deeply injected; while the crystalline area with fewer molecular chain breaks has a higher density and more atomic nuclei. Under the subsequent copper ion injection, the copper ion nuclear collision stopping effect is good, and the copper ion injection is shallow. This lays the foundation for the selective etching of the subsequent copper ion injection. If the argon ion injection time of the first process is too long, it will cause sputtering and deposition of too many target elements, affecting the subsequent selective etching of copper ions, making it difficult to form a nanostructured surface and not conducive to the improvement of the antibacterial effect.

[0011] Preferably, the second step is placed at room temperature for 12 to 48 hours, where room temperature can be understood as ambient temperature.

[0012] Preferably, the copper ion injection time of the third step is 60 to 120 minutes. Due to the biological effect of copper ions, it is preferred to control the copper content in the polyetheretherketone material within a certain concentration range. By controlling the copper ion injection time of the third step, it is possible to avoid excessive copper ion concentration leading to the biological toxicity of the polyetheretherketone material, and it is also beneficial to improve the biological activity and antibacterial properties of the polyetheretherketone material.

[0013] Preferably, the method further includes a fourth step of injecting argon ions after the third step; the argon ion injection time of the fourth step is 30 to 120 minutes; more preferably, the method further includes a fifth step of injecting copper ions after the fourth step; the copper ion injection time of the fifth step is 60 to 180 minutes; further preferably, the method further includes a sixth step of injecting argon ions after the fifth step; the argon ion injection time of the sixth step is 30 to 120 minutes.

[0014] Preferably, the process parameters of argon injection are: argon pressure is 1×10 -1 ~1Pa, the argon injection bias voltage is 400~1000V, the argon injection bias duty cycle is 20~40%, and the argon injection plasma source power is 200~400W.

[0015] Preferably, the process parameters of copper ion implantation are: the background vacuum of copper implantation is 3×10 -3 ~6×10 -3 Pa, argon pressure is 1×10 -2 ~1×10 -1 Pa, the copper injection voltage is 15-40 kV, the copper injection pulse width is 50-600 μs, the copper injection pulse frequency is 5-10 Hz, and the cathode source trigger pulse width is 500-2000 μs.

[0016] Preferably, the argon ion implantation is argon ion sputtering iron ion implantation; during the argon ion implantation process, the iron ions on the sample stage are sputtered and implanted into the surface of the polyetheretherketone material along with the iron ions. That is, during the etching process, the iron elements on the sample stage are sputtered, and the iron elements wrap the copper elements to reduce the cytotoxicity of copper. In addition, the iron elements also have biological activity, so the biocompatibility of polyetheretherketone can be greatly improved, and at the same time, it has good antibacterial properties.

[0017] In a second aspect, the present invention provides a polyetheretherketone surface composition obtained by any of the methods described above, wherein the polyetheretherketone surface composition has an average roughness value of less than 0.3 μm.

[0018] Preferably, the polyetheretherketone surface composition is in the form of nanoparticles with a particle size between 50 and 200 nm, and the nanoparticles occupy more than 80% of the area of ​​the polyetheretherketone material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1a The SEM images of PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr, of which the left image is the top view SEM image and the right image is the side view SEM image;

[0020] Figure 1b This is the high-magnification side-view scanning electron microscope morphology of ArCuAr;

[0021] Figure 2 is the XPS surface element content of PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr;

[0022] Figure 3a It is the full XPS spectrum of PEEK, ArCu, and ArCuAr;

[0023] Figure 3b It is the full XPS spectrum of ArCuAr at different depths;

[0024] Figure 4 It is a schematic diagram of the formation of the surface microstructure of polyetheretherketone modification;

[0025] Figure 5 It is the surface SEM images of PEEK, Ar, ArAr, and CuAr;

[0026] Figure 6 is the copper ion release curve of PEEK, ArCu, ArCuAr, and ArAr in Tris-HCl;

[0027] Figure 7 is the iron ion release curve of PEEK, ArCu, ArCuAr, and ArAr in Tris-HCl;

[0028] Figure 8 is the water contact angle of PEEK, Ar, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr surfaces;

[0029] Fig. 9 It is the curve of zeta potential change with pH on the surface of PEEK, Ar, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr;

[0030] Fig.10 It is the statistical result of the colony count of Escherichia coli cultured in Ar, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr experimental groups;

[0031] Fig.11 are the surface SEM images of E. coli cultured in PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr experimental groups;

[0032] Fig.12 It is the statistical result of the colony count of Staphylococcus aureus cultured in ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr experimental groups;

[0033] Fig.13 are the surface SEM images of Staphylococcus aureus cultured in PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr experimental groups;

[0034] Fig.14a is the SEM images of the adhesion morphology of MC3T3-E1 osteoblasts cultured in the PEEK, ArCu, and ArCuAr experimental groups for 1 h, 4 h, and 24 h;

[0035] Fig.14b is the scanning electron microscopy images of the adhesion morphology of MC3T3-E1 osteoblasts cultured in the ArCuArCu and ArCuArCuAr experimental groups for 1 h, 4 h, and 24 h;

[0036] Fig.15 These are the statistical results of MC3T3-E1 cell proliferation experiments with PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr;

[0037] Fig.16 These are the statistical results of HUVECs cell proliferation experiments with PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr;

[0038] Fig.17 These are the statistical results of rBMSCs cell proliferation experiments on PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr;

[0039] Fig.18a It is the statistical result of quantitative experiment of ALP activity of rBMSCs cells in PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr;

[0040] Fig.18b These are the ALP staining results of rBMSCs cells in PEEK, ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr. DETAILED DESCRIPTION

[0041] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. In the absence of special instructions, each percentage content refers to the percentage content by mass.

[0042] In view of the problems of poor bone integration and lack of antibacterial property of existing medical polyetheretherketone materials, the present disclosure provides a method for surface modification of polyetheretherketone materials. The method includes copper / argon binary ion implantation on the surface of polyetheretherketone materials by plasma immersion ion implantation technology. The purpose of argon ion implantation is to etch the surface of polyetheretherketone and form a unique particle structure (e.g., peanut-like nanoparticle structure), which is conducive to increasing the avoidance (contact) area of ​​polyetheretherketone materials, while sputtering iron elements onto the surface of polyetheretherketone, covering copper elements, and regulating the release of copper ions. The purpose of copper ion implantation is to introduce copper elements that impart biological activity and antibacterial properties to the surface of polyetheretherketone after etching. After ion implantation, copper elements are enriched on the surface, iron elements are sputtered, and biologically active and antibacterial coatings are constructed.

[0043] The method for surface modification of polyetheretherketone material according to the present invention is described in detail below.

[0044] The first step is to implant argon ions on the surface of the polyetheretherketone material by plasma immersion implantation. The first step of argon ion implantation is to clean the sample surface and activate the surface, break some molecular chains on the surface, and prepare for subsequent copper ion implantation and selective etching.

[0045] The polyetheretherketone material may be a medical polyetheretherketone material, such as a pure polyetheretherketone material. Before use, the polyetheretherketone material is polished and then cleaned with acetone and alcohol in sequence.

[0046] The argon ion implantation time of the first step is 10 to 20 minutes. The process parameters of argon ion implantation include: argon injection pressure 1×10 -1 ~1Pa, the argon injection bias voltage is 400~1000V (preferably 600~900V), the argon injection bias duty cycle is 20~40%, and the argon injection plasma source power is 200~400W. In one embodiment, the process parameters for argon ion implantation by plasma immersion ion implantation technology include: the argon injection argon gas pressure is 8.0×10 -1 Pa, the argon injection bias voltage is 800 V, the argon injection bias duty cycle is 30%, and the argon injection plasma source power is 300 W.

[0047] The second step is to place the polyetheretherketone material with argon ion implanted on the surface for a period of time. The polyetheretherketone material after argon ion implantation is placed for more than 12 hours, preferably 12 to 48 hours. More preferably, the polyetheretherketone material after argon ion implantation is placed in a dry environment at room temperature for 24 to 48 hours.

[0048] The third step is to inject copper ions into the surface of the polyetheretherketone material by plasma immersion. The copper ion injection time of the third step is 60 to 120 minutes. The process parameters of copper ion injection include: the background vacuum degree is 3×10 -3~5×10 -3 Pa, argon pressure is 1×10 -2 ~1×10 -1 Pa, copper injection voltage is 15-40 kV, copper injection pulse width is 50-600 μs, copper injection pulse frequency is 5-10 Hz, cathode source trigger pulse width is 500-2000 μs. In one embodiment, the process parameters of plasma immersion ion implantation of copper ions include: copper injection background vacuum degree is 5.0×10 -3 Pa, argon pressure is 6×10 -2 , the copper injection voltage is 15 kV, the copper injection pulse width is 500 μs, the copper injection pulse frequency is 8 Hz, and the cathode source trigger pulse width is 600 μs.

[0049] The sample stage material used for argon ion implantation is stainless steel or pure iron, preferably pure iron. During the argon ion implantation process, the iron element in the sample stage is sputtered, causing the iron element to be sputtered and deposited on the surface of the polyetheretherketone, and the iron element covers the surface of the polyetheretherketone to form an iron oxide film.

[0050] Pure metallic copper can be used as the cathode during copper ion implantation.

[0051] In particular, the order of the first and third steps cannot be interchanged. The reason is that argon ion bombardment can break the molecular chain of polyetheretherketone and carbonize it, while copper ion implantation selectively etches the amorphous area and carbonizes the crystalline area to form a specific surface morphology. If the order of the first and third steps is swapped, the biological activity effect will be partially affected, and even the particle composition and morphological characteristics of the surface of the modified material cannot be formed.

[0052] The surface of the polyetheretherketone modified material obtained by the method of the present invention has an average roughness value (Sa value) lower than 0.3 μm. It can be found from the microscopic morphology that the surface of the polyetheretherketone modified material has a nanoparticle structure. The particle size can be in the range of 50 to 200 nm. The morphology of the nanoparticles is preferably peanut-like particles. The nanoparticles are densely arranged on the surface of the polyetheretherketone material, occupying more than 80% of the surface area of ​​the polyetheretherketone material, which increases the surface area of ​​the material, makes it easier to contact with bacteria, improves the antibacterial effect, and increases the cell binding sites, which helps the adhesion and spreading of cells.

[0053] In some embodiments, the particles on the surface of the polyetheretherketone modified material are composed of a composition containing corresponding single substances and / or oxides of copper and iron elements.

[0054] The MC3T3-E1 osteoblast proliferation effect on the surface of the polyetheretherketone material obtained by the modification method of the present invention is significantly better than that of the unmodified polyetheretherketone, and has good antibacterial properties against Staphylococcus aureus and Escherichia coli, thereby achieving simultaneous improvement of the bone integration and antibacterial properties of medical polyetheretherketone materials, and meeting the actual clinical needs of medical polyetheretherketone. Specifically, the results of the MC3T3-E1 osteoblast adhesion and proliferation experiments confirmed that the polyetheretherketone material obtained by the modification treatment of the present invention has good cell compatibility, and the adhesion and proliferation of MC3T3-E1 cells on the modified surface are significantly higher than those on the unmodified surface. Antibacterial experiments confirmed that the surface of the polyetheretherketone material obtained by the treatment of the present invention has different degrees of antibacterial properties against Staphylococcus aureus and Escherichia coli.

[0055] Of course, the method may also include other steps.

[0056] For example, the fourth step of injecting argon ions after the third step is performed. Since argon ions do not react with the surface of polyetheretherketone, the biological activity of the material is improved by etching and sputtering target elements on the surface of the material, so the present invention has no special restrictions on the injection time of the argon ions. For example, the injection time of the argon ions in the fourth step is 30 to 120 minutes.

[0057] A fifth step of implanting copper ions may be performed after the fourth step. The copper ion implantation time in the fifth step is 60 to 180 minutes.

[0058] It is even possible to carry out a sixth step of injecting argon ions after the fifth step; the argon ion injection time of the sixth step is 30 to 120 minutes.

[0059] Without limitation, argon ion implantation and / or copper ion implantation may be continued after the sixth process. It is only necessary to perform argon ion implantation and copper ion implantation alternately. The last process may be argon ion implantation or copper ion implantation.

[0060] Since excessively high content of copper ions can cause biological toxicity, the total time for copper ion injection in the method of the present invention is preferably controlled within 300 minutes.

[0061] It is explained here that the morphology of the nanoparticles can be adaptively changed according to the injection process. For example, at least 50% of the nanoparticles are optionally single ellipsoidal peanut-shaped particles. Some nanoparticles are peanut-shaped particles formed by connecting two or more ellipsoids. In some embodiments, there is an obvious gap of more than 2nm between the (tandem ellipsoidal) peanut-shaped particles and other particles. In addition, it can be observed that the lower hemisphere of at least some of the nanoparticles is connected to the PEEK substrate, and the particles present an ellipsoidal shape of more than 1 / 2. And in some technical solutions, the surface of the modified polyetheretherketone also has nanopores and / or nanogrooves, which presents a multi-level nanostructure composed of nanoparticles, nanogrooves, and nanopores.

[0062] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0063] Example 1

[0064] After polishing, polyetheretherketone with a diameter of 12 mm and a thickness of 1 mm was ultrasonically cleaned with acetone and deionized water in turn, each ultrasonication lasting 30 minutes. After cleaning, it was placed in an oven at 80°C for drying and properly stored for later use. Using plasma immersion ion implantation technology, argon ions were first implanted into the cleaned polyetheretherketone for 15 minutes. The parameters of argon ion implantation were: injection bias 800V, duty cycle 30%, ion source power 300W, argon gas pressure 8.0×10 -1 Pa. After the argon ion implantation, the sample was left for more than 24 hours before copper ion implantation for 60 minutes. The parameters for copper ion implantation were: injection bias 15 kV, pulse width 500 μs, background vacuum 5×10 -3 Pa, argon pressure 5.0×10 -2 Pa, cathode trigger pulse width 600μs, frequency 8Hz. The obtained sample number is ArCu.

[0065] Example 2

[0066] After polishing, polyetheretherketone with a diameter of 12 mm and a thickness of 1 mm was ultrasonically cleaned with acetone and deionized water in turn, each ultrasonication for 30 minutes. After cleaning, it was placed in an oven at 80°C for drying and properly stored for use. Plasma immersion ion implantation technology was used, and argon ion implantation was performed first for 15 minutes. After the injection was completed, it was placed for 24 hours, and then copper ion implantation was performed for 60 minutes. Then, argon ion implantation was performed again for 60 minutes. The parameters of argon ion implantation and copper ion implantation were the same as those in Example 1. The obtained sample was numbered ArCuAr.

[0067] Example 3

[0068] After polishing, polyetheretherketone with a diameter of 12 mm and a thickness of 1 mm was ultrasonically cleaned with acetone and deionized water in turn, each ultrasonication for 30 minutes. After cleaning, it was placed in an oven at 80°C for drying and properly stored for use. Plasma immersion ion implantation technology was used, and argon ion implantation was performed first for 15 minutes. After the injection was completed, it was placed for 24 hours, and then copper ion implantation was performed for 60 minutes. Then, argon ion implantation was performed for 60 minutes. The copper ion implantation was repeated for 60 minutes. The parameters of argon ion implantation and copper ion implantation are the same as those in Example 1. The sample obtained is numbered ArCuArCu.

[0069] Example 4

[0070] After polishing, polyetheretherketone with a diameter of 12 mm and a thickness of 1 mm was ultrasonically cleaned with acetone and deionized water in turn, each ultrasonication for 30 minutes. After cleaning, it was placed in an oven at 80°C for drying and properly stored for use. Plasma immersion ion implantation technology was used, and argon ion implantation was performed first for 15 minutes. After the injection was completed, it was placed for 24 hours, and then copper ion implantation was performed for 60 minutes. This was followed by argon ion implantation for 60 minutes. Repeat the copper ion implantation for 60 minutes and the argon ion implantation for 60 minutes. The parameters of argon ion implantation and copper ion implantation are the same as those in Example 1. The sample obtained is numbered ArCuArCuAr.

[0071] from Figure 1aIt can be seen that: the ArCu surface has an obvious nano-protrusion structure, the protrusion diameter is about 50-100nm, and the protrusions are evenly distributed. The ArCuAr surface has an obvious nano-particle structure, the nano-particle size is about 50-200nm, and the nano-particles are evenly distributed on the surface of the PEEK material. The ArCuArCu surface has an obvious nano-protrusion structure, the protrusion diameter is about 50-200nm, and the distribution is relatively uniform. The ArCuArCuAr surface has obvious nano-particle and porous structures, the nano-particle size is about 100-200nm, and the nano-particles and porous distribution are relatively uniform. From Figure 1b It can be seen that there are relatively narrow and long nanopores with a pore diameter of 20 to 60 nm and a depth of 200 to 300 nm.

[0072] Depend on Figure 2 It can be seen that copper elements can be introduced into the surface of polyetheretherketone by using copper plasma immersion ion implantation, while argon ion implantation will sputter the elements on the sample stage to the surface of the polyetheretherketone matrix, and the sputtering amount is relatively high, forming an oxide film.

[0073] According to the XPS test, copper plasma immersion ion implantation can be used to introduce copper elements into the surface of polyetheretherketone, and copper elements exist in the form of copper oxide; copper / argon binary plasma immersion ion implantation can be used to introduce copper and iron elements into the surface of polyetheretherketone, and the iron content on the sample surface is higher than that of copper; the copper content of ArCu and ArCuAr is higher than that of PEEK, which shows that argon ion implantation can increase the surface copper content to improve the antibacterial property of the material (see Figure 3).

[0074] Figure 4Schematic diagram of surface microstructure formation for polyetheretherketone modification. Polyetheretherketone is a semi-crystalline linear polymer material. The energy transfer of binary nuclear collisions during plasma immersion ion implantation leads to polymer bond breakage. Since the ion energy is much higher than the binding energy of atoms in the polymer, the ions give the primary substitution atoms enough energy (recoil) for subsequent replacement, thereby generating nonlinear cascade collisions, and ultimately leading to the excitation of polymer units by means of energy deposition of electron stop. Considering the lifetime of the "electronic event" lasting up to 10-12 seconds, the excitation is likely to migrate from the core of the orbit to a relatively long distance (up to 100 polymer units) to form an electronic excitation cascade. The relaxation of the excited state leads to the selective breakage of the weakest bond. Therefore, the breakage of chemical bonds in the polymer occurs by nuclear and electronic stop. For polymers with heteroatom-containing functional groups, bond breakage by electronic excitation is particularly significant. In this embodiment, polyetheretherketone is implanted with negative high-voltage Cu ions of 15kV, first resulting in the degradation of ether bonds and ketone groups, and then gradually degassing and crosslinking the activated polyetheretherketone chains and carbonizing them to form biphenyls and condensed aromatic hydrocarbons. H2O is the main released gaseous product. Heterocyclic groups are more resistant to electronic excitation. However, they can also be transformed due to the asymmetric system of delocalized π electrons. Polyaromatic structures with π electrons responsible for increased conductivity are further formed. In general, the energy transferred to the polymer host during injection due to electron stoppage is mainly released in reactions of dehydrogenation and weak bond breaking. These processes lead to the formation of low-quality fragments and depressions, ultimately presenting a specific surface micro-nanostructure.

[0075] Comparative Example 1

[0076] After polishing, polyetheretherketone with a diameter of 12 mm and a thickness of 1 mm was ultrasonically cleaned with acetone and deionized water in turn, each ultrasonication for 30 minutes. After cleaning, it was placed in an oven at 80°C for drying and properly stored for use. Plasma immersion ion implantation technology was used, and argon ion implantation was first performed for 15 minutes. After the implantation was completed, it was left for 24 hours. The parameters of argon ion implantation were the same as those in Example 1. The obtained sample was numbered Ar.

[0077] Comparative Example 2

[0078] After polishing, polyetheretherketone with a diameter of 12 mm and a thickness of 1 mm was ultrasonically cleaned with acetone and deionized water in turn, each ultrasonication for 30 minutes. After cleaning, it was placed in an oven at 80°C for drying and properly stored for use. Plasma immersion ion implantation technology was used, and argon ion implantation was first performed for 15 minutes. After the injection was completed, it was left for 24 hours, and then argon was implanted for 60 minutes. The parameters of argon ion implantation were the same as those in Example 1. The obtained sample was numbered ArAr.

[0079] Comparative Example 3

[0080] After polishing, polyetheretherketone with a diameter of 12 mm and a thickness of 1 mm was ultrasonically cleaned with acetone and deionized water in turn, each ultrasonication lasting 30 minutes. After cleaning, it was dried in an oven at 80°C and properly stored for use. Plasma immersion ion implantation technology was used to first implant copper ions for 60 minutes. Then argon was implanted for 60 minutes. The parameters of argon ion implantation and copper ion implantation were the same as those in Example 1. The sample obtained was numbered CuAr.

[0081] from Figure 5 It can be seen that there is no obvious nanoparticle structure on the surface of Ar, ArAr, and CuAr samples. This shows that the surface morphology of polyetheretherketone cannot be changed by using only argon plasma immersion ion implantation method; accordingly, omitting the first step cannot form the surface morphology.

[0082] Example 5

[0083] A Tris-HCl buffer solution was prepared by using tris (hydroxymethylaminomethane) (Tris) and hydrochloric acid (HCl) solution, and the pH value was adjusted to 7.4 at 25° C. The samples before and after the modification treatment of the present invention were immersed in 8 mL of the above buffer solution, and the solution was taken out and replaced with a new buffer solution at regular intervals. After immersion for 0.5, 1.5, 4, 7, 14 and 21 days, the zinc ion concentration in the solution was tested by an inductively coupled plasma optical emission spectrometer (ICP-OES, Vista AX, Varian, USA). Figure 6 , Figure 7 It shows that the surface Cu element ( Figure 6 ) and Fe ( Figure 7 ) release amount.

[0084] from Figure 6 It can be seen that the Cu release from ArCu and ArCuAr is similar, indicating that the surface structure and Fe ions will not affect the release of Cu ions; there is no obvious Cu ion release from the ArAr surface. Figure 7 It can be seen that the modified samples are similar to the unmodified polyetheretherketone, and there is no obvious release of Fe ions.

[0085] Example 6

[0086] The surface wettability of the material was tested using a static water contact angle tester (Automatic Contact Angle Meter Model SL200B, Solon information technology Co., Ltd, China). 2 μL of ultrapure water was vertically dropped onto the sample surface using a syringe, and the machine's built-in imaging system was used to take photos of the droplets and analyze the contact angle. Three measurement data were taken on the sample to calculate the average value.

[0087] from Figure 8 It can be seen that the surface contact angle of the PEEK sample is about 89.6°; the surface contact angle of the Ar sample is about 32.4°, and the hydrophilicity is greatly improved; the surface contact angle of the ArCu sample reaches 59.1°, indicating that copper ion implantation will reduce the surface hydrophilicity after argon ion pretreatment. As argon continues to be injected, the hydrophilicity of the material surface is re-enhanced and maintained, and the hydrophilicity will not deteriorate with the re-injection of copper.

[0088] Example 7

[0089] The surface zeta potential of the polyetheretherketone material before and after modification was characterized using a zeta potential tester (Anton Parr, Austria). The specific method is as follows: 0.01M hydrochloric acid (HCl) and 0.01M sodium hydroxide (NaOH) were used to adjust the pH value of the potassium chloride (KCl) solution. During the test, the KCl solution flowed along the sample surface under pressure. According to the Helmholtz-Smoluchowski formula, the relative movement of ions in the diffusion layer was calculated to obtain the zeta potential value.

[0090]

[0091] In the formula, ζ represents zeta potential, dU / dP represents the slope of streaming potential / pressure, η, ε, ε0 and K represent electrolyte viscosity, vacuum dielectric constant, dielectric constant and conductivity respectively. Zeta potential (ζ) is automatically calculated by the instrument. The average value of zeta potential is obtained by taking 4 measurement data.

[0092] from Fig. 9It can be seen that at pH = 7.4, the surface zeta potential values ​​of PEEK and Ar samples are approximately -83mV and -30mV, respectively, indicating that the surface zeta potential of the samples after argon ion injection shows an upward trend at pH = 7.4. The surface zeta potential values ​​of ArCu and ArCuArCu samples are approximately -57mV and -55mV, respectively, indicating that the surface zeta potential of the samples after copper ion injection shows a downward trend compared with the Ar sample at pH = 7.4, but is higher than that of the pure PEEK substrate. The surface zeta potential values ​​of ArCuAr and ArCuArCuAr samples are approximately -43mV and -41mV, respectively, indicating that the surface zeta potential of the samples after argon ion injection again shows an upward trend compared with ArCu and ArCuArCu samples at pH = 7.4, but is lower than that of the pure argon injected Ar sample.

[0093] Example 8

[0094] Staphylococcus aureus (S. aureus, ATCC25923) and Escherichia coli (E. coli, ATCC25922) were selected to evaluate the antibacterial activity of ArCu, ArCuAr, ArCuArCu, and ArCuArCuAr. The specific steps are as follows: 1) Place the sample sterilized with 75% ethanol in a culture plate, and take 60 μL of 10 7cfu / mL of bacterial solution was inoculated on the surface of the sample, the humidity was maintained at more than 90%, and the sample was placed in an anaerobic incubator at 36.5°C for 1 day and 3 days respectively; 2) After 1 day and 3 days of incubation, some samples were taken to wash away the bacterial solution on the surface of the sample with 4.5mL of physiological saline, and diluted to a certain concentration; 100μL of the diluted bacterial solution was inoculated on a nutrient agar plate (TSB agar plate is used to culture S.aureus, and LB agar plate is used to culture E.coli); 3) After coating the plate, it was placed in an anaerobic incubator at 36.5°C for 18-24h, the number of surviving colonies was recorded, and the antibacterial rate was calculated according to the following formula: Antibacterial rate = (BA) / A×100%; where: A is the number of colonies on the surface of polyetheretherketone modified by plasma immersion ion implantation, and B is the number of colonies on the surface of PEEK; 3) After 1 day and 3 days of culture, take some samples, fix them with 2% glutaraldehyde at room temperature for 24 hours, and wash them three times with PBS; 5) Dehydrate the fixed cells with gradient alcohol (volume fraction 30%, 50%, 75%, 90%, 95% and 100%); 6) Place the samples in different ratios of alcohol and hexamethyldisilazane (HMDS) mixed solution (volume ratio of alcohol: HMDS = 2:1, 1:1, 1:2 and 100% HMDS) for drying, and the treatment time is 10 minutes each. After the sample is sprayed with gold, the cell morphology on the sample surface is observed by SEM.

[0095] Depend on Fig.10 and Fig.11 It can be seen that the samples have antibacterial properties against Escherichia coli: the number of bacteria on PEEK is relatively large, and the bacterial shapes are full. The number of colonies on the surface of ArCu and ArCuArCu samples is relatively small, and the bacterial shapes are incomplete. The antibacterial rate is more than 50%, indicating that the materials modified by Example 1 and Example 3 have certain antibacterial properties against Escherichia coli. The number of colonies on the surface of ArCuAr and ArCuArCuAr modified samples is very small, the bacteria are dead and broken, and the antibacterial rate can reach 100%, indicating that the materials modified by Example 2 and Example 4 have strong antibacterial properties against Escherichia coli.

[0096] Depend on Fig.12 and Fig.13 It can be seen that the samples have antibacterial properties against Staphylococcus aureus: the number of bacteria on PEEK is large and the bacteria are full in shape, the number of colonies on the surface of the ArCu modified sample is small and the bacteria are incomplete in shape, but the antibacterial rate is less than 50%, indicating that the material modified by Example 1 has a certain inhibition on Staphylococcus aureus but cannot kill bacteria. The number of colonies on the surface of the ArCuAr, ArCuArCu and ArCuArCuAr modified samples is very small, the bacteria die and rupture, and the antibacterial rate can reach 100%, indicating that the materials modified by Examples 2, 3 and 4 have strong antibacterial properties against Staphylococcus aureus.

[0097] Example 9

[0098] MC3T3-E1 osteoblasts were selected and an in vitro cell culture experiment was used to evaluate the cell compatibility of ArCu and ArCuAr. The cell morphology on the surface of the material was observed using SEM. The experimental steps were as follows: 1) The sample sterilized with 75% ethanol by volume was placed in a 24-well culture plate, and 1 mL of 5×10 4 cell / mL MC3T3-E1 cell suspension; 2) Place the cell culture plate in a cell culture incubator with a volume fraction of 5% CO2 and saturated humidity and incubate at 36.5℃ for 18h; 3) Absorb the cell culture medium, wash the sample surface with PBS, move the sample to a new 24-well plate, and continue to culture in the incubator; 4) After 1, 4 and 7 days of cell culture, take out the sample, fix it with 2% glutaraldehyde at room temperature for 24 hours, and wash it three times with PBS; 5) Dehydrate the fixed cells with gradient alcohol (volume fraction 30%, 50%, 75%, 90%, 95% and 100%); 6) Place the sample in a mixed solution of different ratios of alcohol and hexamethyldisilazane (HMDS) (volume ratio of alcohol: HMDS = 2:1, 1:1, 1:2 and 100% HMDS) for drying, and the treatment time is 10min each. After the sample is sprayed with gold, the cell morphology on the sample surface is observed by SEM.

[0099] from Fig.14a and Fig.14b It can be seen that MC3T3-E1 adheres to the surface of the modified sample faster, and a large number of cells adhere to the sample surface in 1 hour. In addition, the pseudopodia of the modified sample cells are more extended and the morphology is more spread, indicating that the modified sample has better cell compatibility.

[0100] Example 10

[0101] MC3T3-E1 osteoblasts, HUVECs endothelial cells and rBMSCs rat bone marrow mesenchymal stem cells were used for in vitro culture experiments to evaluate the cell compatibility of ArCu and ArCuAr. The proliferation of cells on the surface of the material was detected using the AlamarBlueTM (AbD serotec Ltd, UK) kit. The method is as follows: 1) The sample sterilized with 75% ethanol was placed in a 24-well culture plate, and 1 mL of 5×10 4 cell / mL MC3T3-E1 cell suspension; 2) Place the cell culture plate in a cell culture incubator with a volume fraction of 5% CO2 and saturated humidity and incubate at 36.5℃ for 18h; 3) Remove the cell culture medium, wash the sample surface with PBS, move the sample to a new 24-well plate, and continue to culture in the incubator; 4) After 1, 4 and 7 days of cell culture, remove the original culture medium and add 5% AlamarBlue TM5) Use a microplate reader (BIO-TEK, ELX800) to measure the fluorescence excitation intensity of each well at an incident wavelength of 560nm and an absorption wavelength of 590nm. Calculate cell proliferation according to the following formula: Cell proliferation = A-A'. Where A is the absorbance value and A' is the absorbance value of the negative control well.

[0102] Fig.15 The above are the statistical results of the MC3T3-E1 osteoblast proliferation experiment of the polyetheretherketone modified by Example 1, Example 2, Example 3 and Example 4 and the unmodified polyetheretherketone. It can be seen that the proliferation of MC3T3-E1 cells on the surface of the polyetheretherketone modified by the above Example 1 is not significantly different from that of the unmodified sample, while the proliferation of MC3T3-E1 cells on the surface of the polyetheretherketone modified by the above Example 2, Example 3 and Example 4 is significantly better than that of the unmodified sample, indicating that the modified samples have no obvious cytotoxicity and can promote osteoblast proliferation.

[0103] Fig.16 The statistical results of the HUVECs endothelial cell proliferation experiment of polyetheretherketone obtained by modification treatment in Example 1, Example 2, Example 3 and Example 4 and unmodified polyetheretherketone. It can be seen that endothelial cells are significantly affected by the Cu content. The longer the Cu injection time, the higher the Cu content, and the more endothelial cells proliferate; Ar ion bombardment will sputter off part of the Cu on the surface, so compared with the ArCu sample, the ArCuAr sample has a reduced effect on promoting the proliferation of endothelial cells. However, when the Cu content reaches a certain level (continue copper ion injection), Ar treatment will promote cell proliferation, which may be due to the formation of micro-nano structures and active functional groups on the surface.

[0104] Fig.17 The results are statistical results of rBMSCs rat bone marrow mesenchymal stem cell proliferation experiments on polyetheretherketone modified by Example 1, Example 2, Example 3 and Example 4 and unmodified polyetheretherketone. It can be seen that the proliferation of rBMSCs cells on the surface of polyetheretherketone modified by Example 1, Example 2, Example 3 and Example 4 is significantly better than that of the unmodified sample, indicating that the modified sample has no obvious cytotoxicity and can promote stem cell proliferation.

[0105] Embodiment 11

[0106] The rBMSCs rat bone marrow mesenchymal stem cells were selected to evaluate the cell compatibility of the polyetheretherketone materials modified by the above-mentioned Examples 1, 2, 3 and 4 by in vitro cell culture experiments. The osteogenic differentiation effect of rBMSCs stem cells on PEEK materials before and after modification was evaluated by alkaline phosphatase ALP activity. The experimental steps are as follows: 1) The sample sterilized with 75% ethanol by volume was placed in a 24-well culture plate, and 1 mL of 1×10 4 cell / mL of rBMSCs cell suspension; 2) placing the cell culture plate in a cell culture incubator with a volume fraction of 5% CO2 and saturated humidity and incubating at 36.5°C for 18 hours; 3) aspirating the cell culture medium, washing the sample surface with PBS, moving the sample to a new 24-well plate, and placing it in an incubator for continued culture; 4) after 7 days of cell culture, taking out the sample and measuring the ALP activity of the rBMSCs cells using an alkaline phosphatase kit (Shanghai Bioengineering Co., Ltd.).

[0107] FIG. 18 is a graph showing the ALP activity of rBMSCs cells on the surface of polyetheretherketone before and after modification by the present invention ( Fig.18a ) and ALP staining effect ( Fig.18b ). It can be seen that the ALP activity of the ArCu sample is not much different from that of the unmodified PEEK, while the ALP activity of the ArCuAr and ArCuArCu samples is significantly improved, showing a trend of promoting the osteogenic differentiation of stem cells, indicating that the synergistic effect of the combination of Cu and Fe elements and the surface micro-nano structure is beneficial to improving the bone healing effect of polyetheretherketone.

[0108] In summary, after argon ion implantation, copper ion implantation is performed, the chain segments of polyetheretherketone are broken and then cross-linked, and the surface density of PEEK changes in the process. The radiation damage and thermal damage of copper ion implantation have obvious effects on polyetheretherketone with low surface density. However, the crystalline PEEK structure is compact and can effectively resist the collision compaction of the implanted ions, thus forming a gully-like structure. The subsequent argon injection produces sputtering and carbonization. Ar ions sputter and etch the surface copper oxide and polyetheretherketone. At the same time, polyetheretherketone is carbonized and nucleates and grows around carbon-rich clusters. Therefore, copper and copper oxides are enriched on the surface of polyetheretherketone, which increases the copper concentration on the surface of the material and makes the sample have better antibacterial effect. The sputtered iron and the generated iron oxide cover the surface of polyetheretherketone, avoiding direct contact between copper and cells, making the sample more biocompatible. At the same time, due to the formation of nanoparticle structure on the surface of the material, the surface area of ​​the material is increased, and the contact area between the material and bacteria and cells is increased, thereby improving the antibacterial properties of the material, and promoting the adhesion and proliferation of cells on the surface of the material, and promoting the osteogenic differentiation of stem cells, reflecting the synergistic effect of the material surface composition.

[0109] Industrial Applicability

[0110] The method of the present invention is simple and easy to control. The polyetheretherketone material obtained by the modification treatment of the present invention can obtain different nanostructures on its surface, and its biocompatibility is significantly improved. It has potential prospects for loading bone-inducing growth factors and antibacterial drugs, and can meet the performance requirements of medical polyetheretherketone.

Claims

1. A method for surface modification of polyetheretherketone material, characterized in that: The method comprises: A first step of injecting argon ions into the surface of the polyetheretherketone material by plasma immersion injection; the argon ion injection time of the first step is 10 to 20 minutes; The second step is to place the polyetheretherketone material with argon ions injected on the surface for a period of time; the placement environment of the second step is room temperature, and the placement time is 12 to 48 hours; A third step of plasma immersion implanting copper ions on the surface of the polyetheretherketone material after placement; and a fourth step of implanting argon ions after the third step; Wherein, the argon ion implantation is argon ion sputtering iron ion implantation; during the argon ion implantation process, the iron ions on the sample stage are implanted into the surface of the polyetheretherketone material through sputtering accompanied by argon ions.

2. The method according to claim 1, characterized in that The copper ion implantation time in the third step is 60 to 120 minutes.

3. The method according to claim 1, characterized in that The argon ion implantation time in the fourth step is 30 to 120 minutes.

4. The method according to claim 1, characterized in that: The method further comprises a fifth step of injecting copper ions after the fourth step; the copper ion injection time of the fifth step is 60 to 180 minutes.

5. The method according to claim 4, characterized in that The method further comprises a sixth step of injecting argon ions after the fifth step; the argon ion injection time of the sixth step is 30 to 120 minutes.

6. The method according to claim 1, characterized in that The process parameters of the argon injection are: the argon pressure is 1×10 -1 ~1Pa, the argon injection bias voltage is 400~1000V, the argon injection bias duty cycle is 20~40%, and the argon injection plasma source power is 200~400W.

7. The method according to claim 1, characterized in that The process parameters of the copper ion implantation are as follows: the background vacuum of the copper implantation is 3×10 -3 ~6×10 -3 Pa, argon pressure is 1×10 -2 ~1×10 -1 Pa, the copper injection voltage is 15-40 kV, the copper injection pulse width is 50-600 μs, the copper injection pulse frequency is 5-10 Hz, and the cathode source trigger pulse width is 500-2000 μs.

8. The polyetheretherketone surface composition obtained by the method according to any one of claims 1 to 7, characterized in that The average roughness value of the polyetheretherketone surface composition is below 0.3 μm; the polyetheretherketone surface composition is in the form of nanoparticles with a particle size between 50 and 200 nm, and the nanoparticles occupy more than 80% of the area of ​​the polyetheretherketone material.